In vitro assessment of selenium bioavailability from selenized lactic acid bacteria using a static INFOGEST digestion model and intestinal permeability model - Mrvikova, Iva; Hyrslova, Ivana; Nesporova, Vera; Lampova, Barbora; Cejpova, Klara; Doskocil, Ivo; Musilova, Sarka; Cihlar, Jaromir; Krausova, Gabriela; Kana, Antonin; Kieliszek, Marek (Journal of trace elements in medicine and biology, 2025)
BACKGROUND AND OBJECTIVE: Microbial selenium (Se) supplementation is an essential area of biotechnological research due to differences in the bioavailability and toxicity of different forms of selenium. To date, research has focused mainly on the use of selenized yeast. However, in recent years, scientific interest has also increased in other microorganisms, such as lactic acid bacteria (LAB), which have several unique properties that can affect the quality and bioavailability of selenium. LAB, unlike yeast, can also act as probiotics, which may bring additional health benefits related to improving the intestinal microbiota and supporting the health of the gastrointestinal tract. METHODS: This study investigates the in vitro bioaccessibility and bioavailability of Se from two lactic acid bacterial strains, Streptococcus thermophilus CCDM 144 and Enterococcus faecium CCDM 922 A. We evaluated Se accumulation, speciation, and stability during simulated gastrointestinal digestion and Se permeation through a Caco-2 cell monolayer model. RESULTS: Both strains accumulated Se, metabolizing it predominantly into selenium nanoparticles (SeNPs, 64-77 % of total Se), with only a minor fraction (<5 % of total Se) of organic Se species. Experiments revealed that while organic Se species had high bioavailability (up to 90 %), their bioaccessibility during digestion was very low (<0.1 % of total Se). In contrast, SeNPs showed high bioaccessibility (∼90 %) and moderate transport efficiency through the intestinal model (16-19 % after 4 hours). CONCLUSION: These results highlight the potential of SeNPs produced by lactic acid bacteria as a bioaccessible form of Se for dietary supplementation. Further research is required to explore the behavior of SeNPs within the human body to fully understand how they can be used safely and effectively in nutrition or other applications.
Keywords: lidé; Models, Biological; Caco-2 Cells; selenium nanoparticles; Selenium; biologická dostupnost; Intestinal Barrier Function; Caco-2 buňky; Digestion; permeabilita; Humans; Permeability; selen; Caco-2 cells; funkce střevní bariéry; biologické modely; Enterococcus; Lactobacillales; Enterococcus faecium; Streptococcus; Se species stability; Streptococcus thermophilus; Biological Availability; trávení